2017
DOI: 10.2147/opth.s142075
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a hydrogel corneal inlay and monovision laser in situ keratomileusis in presbyopic patients: focus on visual performance and optical quality

Abstract: PurposeTo compare the visual performance and optical quality after Raindrop Near Vision Inlay implantation or monovision LASIK for the correction of presbyopia.Materials and methodsIn this retrospective case-series study, patients previously treated in the nondominant eye with monovision LASIK were compared with patients previously implanted with Raindrop Near Vision Inlay. The study enrolled 16 inlay and 15 monovision LASIK patients. Uncorrected near visual acuity, uncorrected distance visual acuity, binocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In contrast, some of the older patients with decreased UNVA may struggle to adapt and accept the visual compromises inherent in presbyopia. This group also eventually need driving glasses and daily glasses, even after successful surgery due to declining visual function with age [27][28][29][30][31][32][33][34][35][36][37]. Older patients may also experience response shifts [20]; their SHS score was greater than that of the younger group at baseline, initially increasing, but then continuously decreasing until there was no difference with the younger group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, some of the older patients with decreased UNVA may struggle to adapt and accept the visual compromises inherent in presbyopia. This group also eventually need driving glasses and daily glasses, even after successful surgery due to declining visual function with age [27][28][29][30][31][32][33][34][35][36][37]. Older patients may also experience response shifts [20]; their SHS score was greater than that of the younger group at baseline, initially increasing, but then continuously decreasing until there was no difference with the younger group.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous repeats have associated satisfaction with LASIK and age, complications, and uncorrected distance visual acuity (UDVA) [21][22][23][24]. We hypothesized that anisometropia could be another factor contributing to the decline of satisfaction and happiness that may happen in some patients due to ocular conditions, surgical complications, and intentional monovision for presbyopic LASIK [27][28][29][30]. Anisometropia after LASIK could be a significant issue, both in unexpected and expected cases.…”
Section: Introductionmentioning
confidence: 99%
“…Castro et al simulated the anisocoria generated by corneal inlays using a small aperture contact lens and demonstrated a significant deterioration of stereo-acuity for near and intermediate distances [ 13 ]. Also, studies with LASIK monovision demonstrated that in a proportion of these patients, stereo-acuity is lost and that once lost, it does not recover [ 11 , 14 , 15 ]. Our results were similar to those of Reinstein et al, who found that although postoperative uncorrected stereo-acuity was lower than preoperative near-corrected stereo-acuity after LBV, a functional level of stereo-acuity was maintained postoperatively; 68% of patients had stereo-acuity of 100 sec or better and 93% had stereo-acuity of 200 sec or better [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intracorneal refractive inlays have been used for the correction of presbyopia. 1–7 Among reported complications with their clinical use are infection, abnormal wound healing leading to corneal haze, dislocation, decentration, and keratolysis that may necessitate explantation. 8–11 In this report, we describe a serious vision-threatening complication after the implantation of a presbyopic inlay in combination with hyperopic laser in situ keratomileusis (LASIK).…”
mentioning
confidence: 99%